Association Between Mental Health and Oral Health Status and Care Utilization - Tiwari, Tamanna; Kelly, Abigail; Randall, Cameron L.; Tranby, Eric; Franstve-Hawley, Julie (Frontiers in Oral Health, 2022)
Studies have shown that mental health and oral health may be correlated, with associations demonstrated between mental health problems and tooth loss, periodontal disease, and tooth decay. The COVID-19 pandemic had alarming implications for individuals' and communities' mental and emotional health. This study examined the associations between mental health status, oral health status, and oral healthcare utilization and highlighted the impact of COVID-19 on mental health. Additionally, this study examines specific sociodemographic factors that may amplify oral health disparities. A nationally representative survey was conducted to capture attitudes, experiences, and behaviors related to oral health, mental health, and unmet oral health needs. Eighteen percent of respondents were categorized as having poor mental health. Visiting the dentist in the last year was more common amongst individuals with good mental health. From the logistic regression model, mental health status, age group, race/ethnicity, education, and last dental visit were all significantly associated with of oral health status. Mental health status, age group, and income groups were all significantly associated with unmet oral health need. Future work should focus on the mental-oral health association, including determining ways to improve oral healthcare utilization and oral health status among people with poorer mental health.